Kontribusi Inovasi Kelapa Sawit dan Perlindungan Melalui Hak Kekayaan Intelektual terhadap Krisis Komoditas Ekspor - Ade Maulia Cahyani; Aditya Catur Pamungkas; Galuh Rizky; Isyana Alif Marthani; Ribka Yuniar; Suaibatul Aslamiyyah; Yuliana Yuliana (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
The palm oil industry is a vital component of Indonesia's economy, significantly contributing to foreign exchange earnings and employment opportunities, particularly in rural and plantation-based regions where economic alternatives are limited. However, the sector is increasingly challenged by global sustainability concerns, particularly the European Union Deforestation Regulation (EUDR), which poses a threat to Indonesia’s palm oil exports due to its strict environmental standards and traceability requirements. This study adopts a descriptive qualitative approach using a literature review to explore the role of innovation and legal protection in strengthening the sustainability and global competitiveness of Indonesia’s palm oil industry. Specifically, it investigates how the development of superior plant varieties and the application of Plant Variety Protection (PVP) under the Intellectual Property Rights (IPR) framework contribute to long-term industry resilience. The findings indicate that superior varieties such as DxP Topaz, DxP PTPN V, and Lonsum DxP have been instrumental in boosting productivity, reducing the need for land expansion, enhancing oil yield per hectare, and improving overall resource efficiency. Moreover, legal protection through PVP not only secures exclusive rights for breeders but also incentivizes further agricultural innovation and prevents the unauthorized use and duplication of valuable genetic resources. In light of international regulatory pressures, strengthening the national PVP system, promoting the registration of local superior varieties, and integrating legal instruments with research and development are essential. These efforts can safeguard Indonesia’s genetic sovereignty and support sustainable practices in compliance with international environmental standards. Ultimately, aligning agricultural innovation with a robust legal framework is key to maintaining the industry’s market access, environmental credibility, and long-term sustainability.